The Sacking of Fallujah : A People's History - Shepherd, Jeffrey P., 1970- (Book collections on Project MUSE., 2019)
"The Guadalupe Mountains stand nearly 9,000 feet tall, spanning the far western fringe of Texas, the border of New Mexico, and the meeting point of the Southern Plains and Chihuahuan Desert. Long an iconic landmark of the Trans-Pecos region, the Guadalupe Mountains have played a critical role for the people in this beautiful corner of the Southwest borderlands. In the late 1960s, the area was finally designated a national park. Drawing upon published sources, oral histories, and previously unused archival documents, Jeffrey P. Shepherd situates the Guadalupe Mountains and the national park in the context of epic tales of Spanish exploration, westward expansion, Native survival, immigrant settlement, the conservation movement, early tourism, and regional economic development. As Americans cope with climate change, polarized political rhetoric, and suburban sprawl, public spaces such as Guadalupe Mountains National Park remind us about our ties to nature and our historical relationships with the environment"--